2023
DOI: 10.1038/s41419-023-05700-8
|View full text |Cite
|
Sign up to set email alerts
|

LncGMDS-AS1 promotes the tumorigenesis of colorectal cancer through HuR-STAT3/Wnt axis

Abstract: Chronic inflammation promotes the tumorigenesis and cell stemness maintenance of colorectal cancer (CRC). However, the bridge role of long noncoding RNA (lncRNA) in linking chronic inflammation to CRC development and progression needs better understanding. Here, we elucidated a novel function of lncRNA GMDS-AS1 in persistently activated signal transducer and transcription activator 3 (STAT3) and Wnt signaling and CRC tumorigenesis. Interleukin-6 (IL-6) and Wnt3a induced lncRNA GMDS-AS1 expression, which was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…LncRNAs are abnormally expressed in various types of cancers, and differentially expressed lncRNAs in plasma or serum have become an emerging focus area in noninvasive diagnostic applications [23], including intrahepatic cholangiocarcinoma [27], gallbladder carcinoma [28], glioblastoma [29], and prostate carcinoma [30]. Although the functions and molecular mechanisms of most lncRNAs are still unknown, increasing evidence has shown that lncRNAs may play important roles in the occurrence, progression, and metastasis of tumors [31,32]. Recently, an increasing number of lncRNAs have been found to be related to the prognosis of PaCa.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are abnormally expressed in various types of cancers, and differentially expressed lncRNAs in plasma or serum have become an emerging focus area in noninvasive diagnostic applications [23], including intrahepatic cholangiocarcinoma [27], gallbladder carcinoma [28], glioblastoma [29], and prostate carcinoma [30]. Although the functions and molecular mechanisms of most lncRNAs are still unknown, increasing evidence has shown that lncRNAs may play important roles in the occurrence, progression, and metastasis of tumors [31,32]. Recently, an increasing number of lncRNAs have been found to be related to the prognosis of PaCa.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that RNF6 increased STAT3 phosphorylation by promoting SHP-1 ubiquitination and degradation, demonstrating that the RNF6/SHP-1/STAT3 axis might be a potential treatment option for tumors. However, studies of the mechanism of action for mitigating CRC progression have been relatively concentrated in the signaling pathways associated with STAT3 and the recruitment of mediated immune cells [62,63]. Transcriptomic KEGG functional enrichment analysis showed that signaling pathways directly related to CRC progression, such as the Toll-like receptor, NOD-like receptor, mTOR, and Hippo signaling pathways, were significantly enriched after Zhang-LL intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Through RNA sequencing (RNA-seq) and mass spectrometry (MS) studies, it was discovered that in CRC cells, GMDS-AS1 physically interacts with the RNA-binding protein HuR. This interaction protects HuR from polyubiquitination and proteasomal degradation, highlighting a crucial mechanism by which GMDS-AS1 contributes to the stabilization of proteins involved in cancer cell proliferation ( 61 ). The lncRNA MNX1-AS1/PPFIA4 activates the downstream AKT/HIF-1α signaling pathway to promote COAD proliferation ( 166 ).…”
Section: Regulation Of Cell Proliferation By Lncrnasmentioning
confidence: 99%
“…Additionally, the transcription factor’s binding to IGHM enhancer 3 (TFE3) increases the transcription of LINC01606 after being recruited to the promoter region of LINC01606 ( 155 ). Ye et al.’s study indicates that the lncRNA GMDS-AS1 and its direct target HuR constitutively activate the STAT3/Wnt signaling pathway and promote the stemness of CRC tumors ( 61 ). Sun et al.…”
Section: Lncrnas Regulate Cancer Cell Stemnessmentioning
confidence: 99%